Clinical investigation on sarcoma in oral and maxillofacial regions: A multicenter retrospective analysis in Japan. Issue 5 (September 2020) - Itoh, Ryuichi; Yamada, Shin-ichi; Hasegawa, Takumi; Yamakawa, Nobuhiro; Denda, Yuya; Otagiri, Hiroki; Okura, Masaya; Yanamoto, Souichi; Akashi, Masaya; Kirita, Tadaaki; Ota, Yoshihide; Umeda, Masahiro; et al.
Abstract: The aim of the present study was to review the treatment outcomes of oral sarcoma in Japan based on a multicenter retrospective analysis. Between January 2001 and December 2015, 30 patients were histologically diagnosed with sarcoma in the oral and maxillofacial regions and retrospectively reviewed. Osteosarcoma was the most common in 6 (20 %) out of 30 cases, followed by 3 cases (10 %) of fibrosarcoma. The average maximum size of the primary tumor was 42.3 ± 18.7 mm (range: 5−80 mm). The mandible was the most common site of the primary tumor and observed in 15 cases (50 %), followed by the maxilla in 12 cases (40 %). Soft tissue sarcoma was noted in 3 cases (10 %). The average follow-up period was 5.6 ± 4.6 years (range, 0.1–14.7 years). Five- and 10-year OS rates were 81.4 and 62.0 %, respectively. Five- and 10-year OS rates in cases that underwent radical surgery were 95.5 and 72.7 %, respectively, and were significantly higher than those treated with non-surgical therapy (p < 0.0001). The early detection and complete surgical resection of primary tumors with adequate surgical margins appears to be important for improving the prognosis of oral sarcoma patients.